Produção da soja e do milho na mesorregião oeste do Paraná: correlação com a legislação e práticas sustentáveis - Blanco, Lallucha Alves (2023)
At the same time, environmental issues occupy a significant space in the political, social and moral spheres. Preserving the environment, making the use of natural resources more sustainable is an essential condition for mitigating the effects of anthropic action. The Western of Paraná mesoregion is known for its production of grains, such as soybeans and corn, and monoculture, which is the system widely used in this production, causes significant environmental impacts. Considering the commercial importance of these grains, quantitative analyzes of these productions were carried out in Brazil and Paraná through the IBGE database, raising the necessary inputs for production and their residues through a Life Cycle Assessment (LCA) study, in which the impacts of these productions on the environment and human health were pointed out. Additionally, the available sustainable practices that make it possible to mitigate these damages to the environment were raised, because in the face of the increasing depletion of natural resources combined with the need to promote sustainable development, the alignment of legislation in favor of the adoption of sustainable practices in the production are essential tools to mitigate damage to the environment and human health. Finally, considering the aforementioned context, it can be concluded that the legislation favored the maximization of soybean and corn production, but considering the impacts of the production of these cultivars on natural resources and human health, there is a need for incentives and investments in the adoption of more sustainable production practices.